2011
DOI: 10.2340/00015555-0984
|View full text |Cite
|
Sign up to set email alerts
|

What Can Hide Under ExophytIc Verrucous Appearance?

Abstract: A 70-year-old Caucasian woman attended our pigmented lesions clinic for routine treatment. On examination, numerous seborrhoeic kératoses were found on her trunk and limbs. She reported that a lesion in the centre of her abdomen had increased in size over the previous year. Clinical examination revealed a symmetric lesion comprising two well distinct areas of pigmentation, one light brown and the other dark brown, and exhibiting a typical exophytic verrucous appearance (Fig. 1). Dermoscopic evaluation of the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In the case of tumors with verrucous presentation, it has been shown that 50% of verrucous melanomas can simulate benign tumors. 5,25,26 Verrucous melanomas are considered a specific histopathologic subtype of melanoma, for which it is mandatory to find hyperkeratosis and pseudoepitheliomatous hyperplasia of the epidermis that is intermingled with atypical melanocytes. On the other hand, the term SK-like melanoma refers to a clinical and/or dermoscopic appearance that makes the melanoma look like SK, being verrucous or not on the histopathology report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of tumors with verrucous presentation, it has been shown that 50% of verrucous melanomas can simulate benign tumors. 5,25,26 Verrucous melanomas are considered a specific histopathologic subtype of melanoma, for which it is mandatory to find hyperkeratosis and pseudoepitheliomatous hyperplasia of the epidermis that is intermingled with atypical melanocytes. On the other hand, the term SK-like melanoma refers to a clinical and/or dermoscopic appearance that makes the melanoma look like SK, being verrucous or not on the histopathology report.…”
Section: Discussionmentioning
confidence: 99%
“…In those cases, the clinical information, with nodular or inflamed appearance, or the given history of changes should lead physicians to rule out squamous cell carcinoma or nodular melanoma even in the absence of suspicious dermoscopic features. In the case of tumors with verrucous presentation, it has been shown that 50% of verrucous melanomas can simulate benign tumors . Verrucous melanomas are considered a specific histopathologic subtype of melanoma, for which it is mandatory to find hyperkeratosis and pseudoepitheliomatous hyperplasia of the epidermis that is intermingled with atypical melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…8f). Dermoscopic clues to the diagnosis of verrucous melanoma include the presence of atypical vessels and irregular pigment distribution (De Giorgi et al, 2011;Gencoglan et al, 2011). Structures such as milia-like cysts and comedo-like openings are very conspicuous and are detected almost immediately without requiring a thorough inspection of the entire lesion.…”
Section: Seborrheic Keratosis-like Lesionsmentioning
confidence: 99%
“…Lesions with benign but unclear features should always be histologically analyzed [17]. Melanoma [18,19] or other skin cancers [20] arising in SK have been reported as well as melanoma and SK collisions [21,22]. Noninvasive optical methods, such as reflectance confocal microscopy (RCM) and optical coherence tomography, have been extensively used to improve accuracy in melanoma diagnosis although in SK-like melanoma the application has been limited due to a frequent clinical-dermoscopic misdiagnosis [23].…”
Section: Introductionmentioning
confidence: 99%